Simulating the sound transmission loss of complex curved panels with attached noise control materials using periodic cell wavemodes. (15th December 2019) - Errico, F.; Tufano, G.; Robin, O.; Guenfoud, N.; Ichchou, M.; Atalla, N.
Abstract: The sound transmission loss of complex curved aircraft panels under diffuse acoustic field excitation is experimentally and numerically studied. Two different aircraft sidewall panels are considered: a thick composite sandwich panel and a thin aluminium panel with stiffening elements (stringers and frames). Both bare configuration and with attached soundproofing material are tested in laboratory conditions in coupled rooms. The numerical approach relies on a wave finite element method including modal order reduction at cell scale and an extension based on the transfer matrix method, for the inclusion of poroelastic treatments. The results obtained show that the proposed numerical scheme is efficient for predicting the sound transmission loss of such complex structures.